THE INFLUENCE OF PRICE AND SERVICE QUALITY ON PURCHASE DECISION OF HONDA CAR AT PT. ISTANA CENDRAWASIH MOTOR SEMARANG - Yasinta Budie Pangestika; Karnowahadi Karnowahadi; Isnaini Nurkhayati (Admisi dan Bisnis, 2019)
The growth of automotive world in Indonesia makes the emergence of many car companies. Competitive advantage is required for companies to compete in the market, one of them by increasing purchasing decisions. The purpose of this research is to analyze the partial and simultaneous influence of price and service quality on purchase decision of Honda car at PT. Istana Cendrawasih Motor Semarang. The data used are primary data obtained by using questionnaire. The sample in this study were 100 customers of the PT. Istana Cendrawasih Motor Semarang. Sampling is done by using purposive sampling. The analysis model used in this research is multiple linear regression. The result of determination coefficient (R Square) showed that 28,7% purchase decision was influenced by price and service quality. The rest was explained by other factors not examined in this research. The result of hypothesis testing shows the variables of price and service quality simultaneously and partially significant influence on purchase decision of Honda car at PT. Istana Cendrawasih Motor Semarang